Sorption of veterinary antibiotics to woodchips - Ajmani, Manu (Kansas State University, 2011)
In the upper Midwest, subsurface tile drainage water is a major contributor of nitrate (NO[subscript]3–N) coming from fertilizers and animal manure. Movement of NO[subscript]3-N through tile drainage into streams is a major concern as it can cause eutrophication and hypoxia conditions, as in the Gulf of Mexico. Denitrifying bioreactors is one of the pollution control strategies to treat contaminated tile drainage water. These bioreactors require four conditions which are: 1) organic carbon source, 2) anaerobic conditions, 3) denitrifying bacteria and 4) influent NO[subscript]3-N. This research focuses on investigating fate of veterinary antibiotics in woodchips commonly used in in-situ reactors. Tylosin (TYL) and sulfamethazine (SMZ) are two veterinary antibiotics which are most commonly used in the United States and can be found in tile water after manure is land applied. Partition coefficients of TYL and SMZ on wood were determined by sorption experiments using fresh woodchips and woodchips from an in situ reactor. It was concluded that the woodchips were an effective means to sorb the veterinary antibiotics leached into the tile water after application of animal manure. Linear partition coefficients were calculated and phase distribution relationships were established for both the chemicals. The fresh woodchips gave inconclusive data but predictions could be made by the information determined in the experiments using woodchips from a ten year old woodchip bioreactor. Desorption was also studied and the likelihood of desorption was predicted using the Apparent Hysteresis Index. Overall, it was found that the old woodchips allowed for quick sorption of both antibiotics. It was also found that SMZ had reversible sorption on old woodchips. Thus, it was concluded that the woodchip bioreactor would not be effective for removal of veterinary antibiotics from tile drainage. More research is required for the fate of TYL and to confirm the conclusion.
Keywords: Sorption/desorption; Tylosin; Sulfamethazine; Woodchip bioreactor; Veterinary antibiotics; Denitrification; Engineering (0537); Engineering, Agricultural (0539); Environmental Engineering (0775)